Raised circulating tenascin-C in rheumatoid arthritis - Page, Theresa H (BioMed Central, 2012)
INTRODUCTION: The aim of this study was to examine whether circulating levels of the pro-inflammatory glycoprotein tenascin-C (TNC) are elevated in musculoskeletal disorders including rheumatoid arthritis (RA) and to assess in RA whether levels are related to clinical disease status and/or patient response to treatment. METHODS: TNC in serum or plasma was quantified by ELISA. Samples from 4 cohorts of RA patients were examined and compared to normal human subjects and to patients with other inflammatory diseases. RESULTS: Circulating TNC levels were significantly raised in patients with RA, as well as patients with systemic lupus erythematosus, idiopathic inflammatory myositis, psoriatic arthritis and ankylosing spondylitis, whilst patients with Sjogren's syndrome displayed levels similar to healthy controls. The highest levels of TNC were observed in RA patients with late stage disease. In early disease TNC levels correlated positively with ultrasound determined erosion scores. Treatment of early RA patients with infliximab plus methotrexate (MTX) resulted in a transient decrease in circulating TNC over the first year of therapy. In contrast, TNC levels increased over time in RA patients receiving MTX alone. In patients treated with infliximab plus MTX, baseline TNC levels significantly correlated with tender joint counts (TJC) at 18 and 54 weeks after initiation of infliximab therapy. CONCLUSIONS: Raised circulating TNC levels are detected in specific inflammatory diseases. Levels are especially high in RA where they may act as a biomarker of bone erosion and a predictor of the effect of infliximab on RA patient joint pain.